Phenylsulfonylfuroxan NO-donor phenols: Synthesis and multifunctional activities evaluation. Issue 16 (15th August 2017) - Xie, Yundong; Yang, Yaping; Li, Sen; Xu, Yanhong; Lu, Wenfang; Chen, Zizhang; Yang, Guangde; Li, Yiping; Cao, Yongxiao; Bian, Xiaoli
Graphical abstract: Abstract: Phenylsulfonyfuroxan nitric oxide (NO)-donor phenols were designed, synthesized and evaluated. The compounds were designed through a symbiotic approach using selected phenols and phenylsulfonylfuroxan NO-donor. The antioxidant activities of the hybrid compoundsT2 –T6 showed to be good in vivo . CompoundsT4 andT6 revealed excellent yeast α-glucosidase inhibitory activity and anti -glycosylation activity. All of the compounds exhibited strong NO releasing activity and significant anti -platelet aggregation activity. The inhibition of platelet aggregation was more than 50% at low concentration (1.5 μM) and 95% at higher concentration (15 μM and 150 μM). The vasodilatation experiment demonstrated that the six compounds under test exhibited definite vasodilation activity (pIC50 ranged from 5.698 to 6.383), especially compoundT6 (pIC50 was 6.383) which was similar to sodium nitroprusside (pIC50 was 6.786). Both anticoagulant and vasodilatation effects were correlated with their NO releasing activities. These hybrid phenylsulfonyfuroxan-based NO-donor phenols offer a multifunctional prodrug design concept for the development of therapeutic or preventive agents for metabolic syndrome.